Masjid Raya Al-Falah Sragen: Pusat Pemberdayaan Umat Penggerak Kemandirian Sosial Dan Ekonomi - Khotimatuzzahro, Khotimatuzzahro; Nafi’, Ahmad (Community Development: Jurnal Pengembangan Masyarakat Islam, 2025)
Al-Falah Grand Mosque, Sragen: A Center For Empowering The People, A Drive For Social And Economic Independence. Mosques have a strategic role not only as a place of worship, but also as a center for education, social, and economic empowerment of the people. Community service (PKM) at the Al Falah Sragen Grand Mosque is carried out as an effort to optimize the function of the mosque through the active involvement of students in various da'wah activities, services, and socio-economic development. A participatory and multidimensional approach that goes beyond the mere function as a place of mahdah worship, thereby strengthening the intensity of interaction between takmir, administrators, and worshippers so that the program designed becomes applicable and sustainable. This activity opens up an optimal learning space for students to integrate theory with real practice in the field while improving communication, leadership, and organizational management skills. The results of PKM show a significant increase in religious awareness, social solidarity, and economic independence of pilgrims. The Al Falah Sragen Grand Mosque has succeeded in becoming a model of mosque management that is responsive to social developments by integrating authentic Islamic values and innovation in sustainable services and economic empowerment.